Between the Promotion of Global Trade and the Protection of Fundamental Rights: An Analysis of the Structural Tensions of the International Economic Regime and States, and Their Impacts on Vulnerable Communities - Hinojosa Congona, Christian Gabriel (2026)
This article examines the structural tensions between the international economic regime and the protection of fundamental rights, with particular attention to their differentiated impacts on vulnerable communities. It analyzes how trade liberalization, investment treaties, and the influence of international economic institutions have progressively reduced States’ regulatory space, undermining the effective protection of labor, social, environmental, and collective rights. Through a doctrinal, critical, and interdisciplinary legal approach, the study highlights the fragmentation of international law, normative asymmetries, and the democratic deficit embedded in the global trade system. It further assesses concrete impacts on workers, Indigenous peoples, women, children, and migrants, emphasizing patterns of precarization, exclusion, and environmental harm. Finally, the article reviews existing mechanisms of State and corporate responsibility and argues for the integration of binding human rights standards into trade and investment agreements as a necessary step toward reconciling economic globalization with social justice and human dignity.